Alcohol Consumption and Risk of Uterine Fibroids - Takala, Hajra; Yang, Qiwei; El Razek, Ahmed M. Abd; Ali, Mohamed; Al-Hendy, Ayman (Current Molecular Medicine, 2020)
Lifestyle factors, such as alcohol intake, have placed a substantial burden on public health. Alcohol consumption is increasing globally due to several factors including easy accessibility of this addictive substance besides its legal status and social acceptability. In the US, alcohol is the third leading preventable cause of death (after tobacco, poor diet and physical inactivity) with an estimated 88,000 people dying from alcohol-related causes annually, representing 1 in 10 deaths among working adults. Furthermore, the economic burden of excess drinking costs the US around 249 billion (191.1 billion related to binge drinking). Although men likely drink more than women do, women are at much higher risk for alcohol-related problems. Alcohol use is also considered to be one of the most common non-communicable diseases, which affects reproductive health. This review article summarizes the current knowledge about alcohol-related pathogenesis of uterine fibroids (UFs) and highlights the molecular mechanisms that contribute to the development of UFs in response to alcohol consumption. Additionally, the effect of alcohol on the levels of various factors that are involved in UFs pathogenesis, such as steroid hormones, growth factors and cytokines, are summarized in this review. Animal studies of deleterious alcohol effect and future directions are discussed as well.
Keywords: growth factors